Nanostructured gas sensors in smart manufacturing - Gorup, Luiz Fernando; Sequinel, Thiago; Akucevicius, Graziele Weirich; Pinto, Alexandre Henrique; Biasotto, Glenda [UNESP]; Ramesar, Naomi; De Arruda, Eduardo Guimarães Ratier; De Arruda, Eduardo José; Camargo, Emerson Rodrigues (Elsevier, 2021)
Gas sensors are used for measuring the concentration of pressure of gases around their vicinity. These sensors are equipped with highly sensitive sensing elements of nanostructured materials. They find extensive application in residences, urban areas, smart farms, military systems, and industries for detecting toxic gases, including hydrogen sulfide, ammonium, carbon monoxide, and several species of nitrogen oxide, or to control the partial pressure of oxygen inside confined spaces, such as submarines, military aircraft, or chambers for hyperbaric treatments. The rise in demand from critical industries for gas sensors is due to environmental regulation of gas emissions or the monitoring of air quality in metropolitan areas due to vehicle emissions; these are the major factors driving the growth of the gas sensors market, which can open new opportunities for small companies in high technology and nanotechnology. The advent of a new era based on the Internet of Things (IoT) in smart cities, residences, and farms, as well as on smartphones and wearable devices, also represents an opportunity for advanced gas sensors. These lower-power, more affordable sensors are becoming available and are being integrated into consumer electronics. Here our emphasis is on highlighting the market segments and the different priorities underlying the choice of environmental sensor, which varies with the application. The principal gas sensors are pellistor sensors, infrared sensors, metal oxide semiconductor (MOS) sensors, electrochemical sensors, and optical particle monitor (OPM) sensors. This chapter summarizes some examples of highly sensitive nanostructured material sensors in smart cities, smart farming, and process and manufacturing industries for detecting various toxic gases, including hydrogen sulfide, ammonium, carbon monoxide, and nitrogen dioxide.
Keywords: Gas sensor; Intelligent agriculture; Nanosensor; Nanostructured materials; Pollution levels; Sensor industry; Smart cities; Smart farming; Smart packaging